On globalization from linguistic point of view - Lotko, Edvard (Bohemica Olomucensia, 2012)
There is need to study the tendencies of language development, sociolinguistic and psycholinguistic processes and pragmalinguistics in the mother language education. Most important topic is to give to users of language information about the current functioning of language as the main instrument of social interaction. Today the Polish linguistics has the rich and actual results in this topic.